Pelatihan dan Pendampingan Hospitality Masyarakat di Desa Taro Gianyar Bali - I Putu Agus Suarsana Ariesta; I Wayan Induyoga Aditama; Ni Putu Mita Andini Dewi (Pubfine Media Group, 2024)
The community training and mentoring program is an activity that consists of two activities, namely training and mentoring the local community. Community training is one of the outreach activities in order to empower the community, especially to improve the knowledge, attitudes and skills of village communities. Community mentoring is an activity aimed at carrying out development and empowerment of village communities. This program aims to provide guidance to the community to form independent community groups. Therefore, the role of students is needed through the Triatma Mulya University KKNT program to carry out community training and mentoring programs in Taro village. In the Taro village community training and mentoring program in the context of implementing the University's KKNT Triatma Mulya, which has been implemented by KKNT students, includes two main programs, namely front office and housekeeping training. This training program was attended by management representatives from all homestays in Taro village. The method used in this program is the observation method, namely through observation, accompanied by notes on the condition or behavior of the target object. The activity ran well and smoothly, successfully providing material that was easy for the invitees to understand and also succeeded in attracting the enthusiasm of the invitees to participate. come and participate in the training program.